Components of Uncertainty - Vegard Høghaug Larsen (Norges Bank, 2017)
Uncertainty is acknowledged to be a source of economic fluctuations. But, does the type of uncertainty matter for the economy's response to an uncertainty shock? This paper offers a novel identification strategy to disentangle different types of uncertainty. It uses machine learning techniques to classify different types of news instead of specifying a set of keywords. It is found that, depending on its source, the effects of uncertainty on macroeconomic variable may differ. I find that both good (expansionary effect) and bad (contractionary effect) types of uncertainty exist.
hdl:11250/2495586
Keywords: D80; E32; E66; 330; newspaper; topic model; uncertainty; business cycles; machine learning